Ketones and pain: unexplored role of hydroxyl carboxylic acid receptor type 2 in the pathophysiology of neuropathic pain. Issue 1 (7th August 2018) - Boccella, Serena; Guida, Francesca; De Logu, Francesco; De Gregorio, Danilo; Mazzitelli, Mariacristina; Belardo, Carmela; Iannotta, Monica; Serra, Nicola; Nassini, Romina; de Novellis, Vito; Geppetti, Pierangelo; Maione, Sabatino; et al.
ABSTRACT: The mechanisms underlying neuropathic pain are poorly understood. Here we show the unexplored role of the hydroxyl carboxylic acid receptor type 2 (HCAR2) in 2 models of neuropathic pain. We used an oral treatment with dimethyl fumarate and the HCAR2 endogenous ligand β‐hydroxybutyrate (BHB) in wild‐type (WT) and HCAR2‐null mice. We found an up‐regulation of the HCAR2 in the sciatic nerve and the dorsal root ganglia in neuropathic mice. Accordingly, acute and chronic treatment with dimethylfumarate (DMF) and BHB reduced the tactile allodynia. This effect was completely lost in the HCAR2‐null mice after a 2‐d starvation protocol, in which the BHB reached the concentration able to activate the HCAR2‐reduced tactile allodynia in female WT mice, but not in the HCAR2‐null mice. Finally, we showed that chronic treatment with DMF reduced the firing of the ON cells (cells responding with an excitation after noxious stimulation) of the rostral ventromedial medulla. Our results pave the way for investigating the mechanisms by which HCAR2 regulates neuropathic pain plasticity.—Boccella, S., Guida, F., De Logu, F., De Gregorio, D., Mazzitelli, M., Belardo, C., Iannotta, M., Serra, N., Nassini, R., deNovellis, V., Geppetti, P., Maione, S., Luongo, L. Ketones and pain: unexplored role of hydroxyl carboxylic acid receptor type 2 in the pathophysiology of neuropathic pain. FASEB J. 33, 1062–1073 (2019). www.fasebj.org